Heritage conservation : an integrated approach. - Koh, Vivian Pey Yng. (2008)
This paper seeks to explore the many aspects of a heritage product and thus develop guidelines that will allow owners of such resources to manage them in a manner that allows for sustained preservation, while simultaneously maintaining a level of contact with society that communicates its inherent identity.